Implementasi Interactive Flat Panel Dalam Meningkatkan Literasi Numerasi Anak Usia Dini - Hartini, Hartini; Nofriyelniati, Nofriyelniati; Khusnia, Alfun (UIN Sultan Maulana Hasanudin Banten, 2026)
This descriptive qualitative study explores the use of innovative Interactive Flat Panel (IFP) technology to enhance early childhood numeracy skills, which are crucial for critical thinking yet often taught passively. The research subjects involved a teacher and 17 students from group B2 (aged 5–6 years) at TK Mutiara YPMK, South Solok. Data were collected through observation, interviews, and documentation. The findings indicate that the touchscreen features of the IFP successfully satisfied students' curiosity, increasing their interest, active engagement, and understanding of basic numeracy concepts (number recognition, quantity, patterns, and basic arithmetic). As a collaborative multisensory medium that integrates the concept of learning through play, IFP is recommended as a progressive learning tool to improve early childhood numeracy literacy.